PENGARUH PERBEDAAN SUHU TERHADAP DAYA TETAS TELUR IKAN KEURLING (Tor soro) - Muhammad Irfandi; Azwar Thaib; Nurhayati Nurhayati (Jurnal TILAPIA, 2020)
The fish Tor Soro or better known among Acehnese people with the name keurling fish is one of freshwater fish. The hatching process generally lasts faster at higher temperatures because at high temperatures the metabolic process runs faster so that the development of the embryo will be faster, resulting in the movement of the embryos in a more intensive shell. The problems that often arise in the hatching of keurling eggs are many eggs that do not hatch due to the temperature that is not suitable. The research draft used in this study is a complete randomized design consisting of 4 treatments and 3 repeats. The results showed that the best temperature in the hatching of Keurling fish eggs was 22 ° C.